Evaluating the Effectiveness of Augmented Reality (AR) Tools for Interactive Learning Experiences in Higher Education - Lesmana, Rudhi (Universitas Komputer Indonesia, 2023)
This study explores the application of Augmented Reality (AR) technologies to enhance interactive learning experiences in higher education environments. Through a combination of literature reviews, case study analyses, and user experience evaluations, the research examines how AR tools contribute to student engagement, conceptual understanding, and overall academic performance. Key findings reveal that AR technologies create immersive and interactive environments that significantly enhance learner motivation and participation. The integration of AR into educational settings also facilitates the visualization of complex concepts, providing students with practical and experiential learning opportunities. However, challenges such as technological limitations, the need for instructor training, and issues related to device accessibility remain critical considerations for widespread adoption. Discussions highlight the transformative potential of AR in reshaping traditional pedagogical models, promoting active learning strategies, and addressing evolving educational demands. Furthermore, the study identifies best practices for effective AR implementation, including aligning AR applications with curricular goals and ensuring ease of use for both students and educators. The conclusions emphasize the growing significance of adopting innovative technologies like AR to improve learning outcomes, foster digital competence among students, and prepare higher education institutions for the future of technology-driven education.